2018
DOI: 10.15171/ijep.2018.26
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Presence and Expression of stx1 Gene in Escherichia coli Isolated From Women With Urinary Tract Infection Using Real-Time PCR in Tabriz, Iran

Abstract: Background Escherichia coli is the most common cause of urinary tract infections (UTIs), especially in young women. 1 E. coli is responsible for more than 80%-90% of UTI among the community and 30%-50% in the hospitals. In addition, this bacterium is one of the main causes of hospitalization with significant complications and high health care costs. 2 The verotoxigenic E. coli (VTEC) strains secrete a type of toxin which is called verotoxin due to its ability in killing Vero cells. Further, because of the simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Evidence suggested that Gram-negative bacteria, especially P. aeruginosa, encodes metallo-β-lactamase enzyme by several transferable genes (12,13). Therefore, the continuous increase in the prevalence of antibiotic-resistant strains has become an important concern (14,15). In the Ambler classification scheme, β-lactamases of classes A, C, and D are serine β-lactamases.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggested that Gram-negative bacteria, especially P. aeruginosa, encodes metallo-β-lactamase enzyme by several transferable genes (12,13). Therefore, the continuous increase in the prevalence of antibiotic-resistant strains has become an important concern (14,15). In the Ambler classification scheme, β-lactamases of classes A, C, and D are serine β-lactamases.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract infection (UTI) is one of the important health problem in women, which usually is occurred due to E. coli . Approximately, 150,000,000 individuals are diagnosed with UTI per year worldwide [1] . UTI is frequently observed with urological problems, which can lead to hypertension of renal failure continued [2] .…”
Section: Introductionmentioning
confidence: 99%